Analysis and Comparison of Linguistic Features of Gender Communication in Italian and Uzbek Literature (Eurasian Journal of Learning and Academic Teaching, 2026)
This article analyzes and compares the linguistic features of gender communication in Italian and Uzbek literature. Gender is examined as a sociocultural phenomenon manifested in the characters' communicative strategies and the linguistic representation of social roles. The study draws on an interdisciplinary approach that combines linguistic, discourse, and comparative analysis. Particular attention is paid to lexical choice, expressive semantics, forms of politeness, speech initiative, and metaphorical means of describing gender relations.